Are Filipino students’ L2 learning goals performance- or masteryoriented? An explanatory sequential analysis - Macayan, Jonathan Veran; Quinto, Edward Jay Mansarate; Otsuka, Julius C.; Cueto, Allyzsa Bernadette S. (Penerbit Universiti Kebangsaan Malaysia, 2018)
Whether students’ goals for learning English as a second language (L2) are oriented towards performing better than others or mastering one’s skills had not been traditionally investigated in language motivational research. Premised on Pintrich’s (2000) revised achievement goal theory, this explanatory sequential research (Creswell, 2014) examined the influence of learners’ goal orientation in L2 to their writing and speaking performances. 162 Filipino students enrolled in an English for Academic Purposes (EAP) course in a University in Manila participated in the study. They initially accomplished the Goal Orientation in A L2 Scale (GOALS) developed to fit the current context, α= .93. Then, they took two language tests, i.e., a group conversation in English for L2 speaking and an individual essay for L2 writing. Both were administered in the EAP classes as an entry requirement. Analyses yielded significant results on the influence of goal orientation on both speaking and writing. Results suggest that students with a performance orientation to L2 learning performed significantly better than those with either a mastery or a multiple goal orientation. In keeping with the sequential design, the researchers proceeded with semi-structured interviews among nine purposefully selected respondents to understand the quantitative results in greater detail. The follow-up interviews focused on two aspects of the statistical results: maladaptive influence of multiple orientation and the adaptive influence of performance orientation in L2 learning. The paper closes with implications for research and language teaching.